Pecalang Regulations Within the Framework of the Village Government System - Ramadhan, Diastama Anggita (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
Pecalang, a traditional village in Bali, is a sub-system in the governance of a traditional village in Bali, whose job is to maintain security and order in the territory of the customary village authority. Pecalang existed before the emergence of village regulations in Indonesia. It becomes a problem when the Pecalang sub-system is viewed from the perspective of village regulations. This problem is studied in this research. The research method used is normative juridical using secondary legal data. The results of the study show that Pecalang based on Article 103 Law No.6/2014 concerning Villages which provides an explanation regarding the Authority of Traditional villages, the presence of customary Pecalang domiciled in each customary village in the Province of Bali already has legality. In addition, Pakraman Village itself has awig-awig and pararem which function as customary village regulations which in it provide arrangements for Pecalang custom This has clearly illustrated that the presence of customary Pecalang is in accordance with the corridors of the village government system with all the relevant laws and regulations that govern it.